Ecology and the evolution of cooperation by partner choice and reciprocity - Marcelino Fuentes (Scientific Reports)
Abstract Organisms help each other to get resources, protection from enemies, and other goods, but not as much as would be best for their population. Partner choice, direct reciprocity and indirect reciprocity foster cooperation and help to align individual interests with the social good. However, we still do not know what ecological variables affect their success and interaction. I simulated the evolution of partner choice, direct reciprocity and indirect reciprocity, and the production of a good that partners donate to each other. I show that, with few exceptions, partner choice evolves whenever there is an initial social dilemma, under a wider range of conditions than direct reciprocity. Direct reciprocity is deleterious when the shared good is highly essential or very influential. Both partner choice and direct reciprocity compel individuals to produce close to the socially optimal quantity of the shared good. Direct reciprocity does so even when it is deleterious and reciprocators are rare. Indirect reciprocity succeeds when individuals can also choose partners, and in most cases contributes less than partner choice or direct reciprocity to alleviating social dilemmas. Partner choice may have allowed humans to use a set of collectively produced goods including clothing, fire, hunting tools, housing, and shared knowledge, to the point that they became essential.